PEMANFAATAN TEPUNG BIJI NANGKA DAN TEPUNG JAGUNG DALAM PEMBUATAN FLAKES - Nurul Hadi; Yusmarini Yusmarini; Raswen Efendi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Flakes was one of the breakfast cereal products favored by the public, because it practical in presentation and  high nutrient content. The content of jackfruit seed flour such as carbohydrates and protein which was high enough, so it could be combined with added corn flour as a source of fat and fiber. The purpose of those research was to obtain the best ratio between the jackfruit seed flour and corn flour  towards quality of flakes. This research was conducted experimentally using a Completely Randomized Design (CRD) with 5 treatments and 3 replications.  The treatment performed were BJ0 (jackfruit seed flour 100%), BJ1 (jackfruit seed flour 90% : corn flour 10%), BJ2 (jackfruit seed flour 80% : corn flour 20%), BJ3 (jackfruit seed flour 70% : corn flour 30%), and BJ4 (jackfruit seed flour 60% : corn flour 40%). The results of chemical analysis and sensory then selected the best treatment was the treatment BJ4 (jackfruit seed flour 60% : corn flour 40%) with moisture 4.17%, ash 2.96%, fat 2.12%, protein 9.26%, carbohydrate 81.48%, and crude fiber 3.19%. Overall to result of sensory test preferred by the panelists with descriptions of pale yellow color, flavorful corn, corn taste, crunchy texture without the added of  milk, and rather than soft texture with the added of milk. Keywords: Flakes, jackfruit seed flour, corn flour.